Progesterone potentially degrades to potent androgens in surface waters - Ojoghoro, Jasper O.; Chaudhary, Abdul J.; Campo Moreno, Pablo; Sumpter, John P.; Scrimshaw, Mark D. (Elsevier, 2016)
Progesterone is a natural hormone, excreted in higher concentrations than estrogens, and has been detected in the aqueous environment. As with other compounds, it is transformed during wastewater treatment processes and in the environment. However, minor modifications to the structure may result in transformation products which still exhibit biological activity, so understanding what transformation products are formed is of importance. The current study was undertaken to identify putative transformation products resulting from spiking river water with progesterone in a laboratory-based degradation study and hence to follow the metabolic breakdown pathways. On the basis of literature reports and predictions from the EAWAG Biocatalysis/biodegradation database, target putative transformation products were initially monitored under unit resolution mass spectrometry. The identity of these transformation products was confirmed by using accurate-mass quadrupole time-of-flight. The study results highlight that transformation of progesterone can potentially create other classes of steroids, some of which may still be potent, and possess other types of biological activity.
Keywords: Progesterone; Steroids; Transformation; Metabolites; Pathways